ВЗАЄМОДІЯ ДОШКІЛЬНОГО НАВЧАЛЬНОГО ЗАКЛАДУ І СІМ’Ї В АСПЕКТІ ФОРМУВАННЯ У ДІТЕЙ ЗДОРОВ’ЯЗБЕРЕЖУВАЛЬНОЇ ПОВЕДІНКИ - Андрущенко, Наталія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядається й уточнюється сутність поняття «взаємодія», «взаємодія дошкільного навчального закладу і сім’ї» як найважливіших інституцій соціалізації і виховання дитини. Автор на основі аналізу наукових поглядів щодо сутності категорії «взаємодія», наголошує на тому, що кардинальні зміни поглядів на цінності сучасної сім’ї, важливі завдання дошкільної освіти вимагають переосмислення традиційних підходів до взаємодії дошкільних навчальних закладів з батьками вихованців. Дослідниця формулює мету та провідні завдання такої взаємодії, що впливають на формування здорового способу життя особистості дитини. В статье рассматривается и уточняется сущность понятий: «взаимодействие», «взаимодействие дошкольного образовательного учреждения и семьи» как самых важных институций социализации и воспитания ребенка. Автор на основании анализа научных взглядов о сущности категории «взаимодействие», акцентирует внимание на том, что кардинальные изменения взглядов на ценности современной семьи, важные задания дошкольного образования требуют переосмысления традиционных походов к взаимодействию дошкольного образовательного учреждения с семьями воспитанников; формулирует цель и задания такого взаимодействия, влияющие на формирование здорового способу жизни личности. In the article the essence and refined the concept of «interaction», «interaction kindergarten and the family» as the most important institutions of socialization and education of the child. The author based on the analysis of scientific views regarding the nature of the category of «interaction», emphasizes that the dramatic changes of views on the modern family values are important objectives of preschool education require rethinking traditional approaches to interaction between pre-schools with parents of pupils. The researcher defines goals and key objectives such interactions affecting the healthy lifestyle of the child. Namely: the disclosure features physical, mental, social and spiritual health of preschool and important example of parents for the education of children retaining health behavior; the need to ensure a favorable psychological atmosphere in the family and humanization of relations between parents and children, maintaining the image of the family as the fundamental principle of education in child care retaining health behavior.